أثر الربحية في القيمة في سوق المال - Abu-Shawer, Munir; Al Ajlouni, Ahmed (مجلة العلوم الإدارية و الإقتصادية, 2018)
The study explores the relationship between the profitability (measured by ROI, ROE and NPR)and the stock market prices of the Petrochemical Industry Firms in Saudi Arabia during the period 2008-2015.We used the multiple regression model to estimate the relationship between the independent variables and the dependent variable by using the Cross Section–Time Series (Panel Data).The study confirms that the stock prices of petrochemical companies listed in the Saudi Stock Market does not reflect the profit performance on the market price of the stocks. The affection trend on the profit performance is varied by different profitability measures.